Pengaruh Literasi Keuangan dan Lingkungan Bisnis terhadap Kinerja Bisnis (Survei pada UMKM) - Nuraini, Reny; Mardikaningsih, Rahayu (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
Digitalization is an economic trend indicated by a wide open market network, the emergence of many entrepreneurs, and various innovations that require MSMEs to have competitive advantages. The achievement of MSMEs being able to compete requires various strengths that are currently still a challenge for MSME actors. The capital needed and the quality of human resources as an important concentration of an MSME pay attention to business performance can run well. The description of this objective is to determine the contribution of managerial skills factors to business performance positively and significantly. The second objective is to determine the contribution of financial literacy factors positively and significantly to business performance. This method is a quantitative descriptive type with a survey category. Data analysis was carried out using multiple linear regression with a sample involving 100 MSME actors in Sidoarjo based on sample determination using purposive sampling. This finding proves the positive and significant contribution generated by managerial skills to business performance. Another finding, business performance is influenced by the effects of financial literacy positively and significantly. The limitation of this study is that the respondents involved can reach a larger sample range.